Implementing efficient and effective learnerships in the construction industry : a study in the building and civil sector of the Western Cape - Mummenthey, Claudia (Stellenbosch : Stellenbosch University, 2008)
Thesis (MComm (Industrial Psychology))--Stellenbosch University, 2008.